PENERAPAN METODE COOPERATIVE LEARNING PADA MATA PELAJARAN SENI BUDAYA DI SMP NEGERI 26 PADANG - Dilla Apriamanda; Syeilendra Syeilendra; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2018)
Abstract The study aims was to describe the application of cooperative learning method in the subjects of art and culture on class VIII.3 in SMP Negeri 26 Padang. The main data sources in this study were students who had given cooperative learning method. Technique of data collection was done by using techniques such as observation, interview, results of the study and library research. This study used a qualitative approach. In applicating the cooperative learning method, there were some steps as follows: in the first meeting, teacher explained traditionalal music material, as well as the divided of the group. The second meeting, teachers shared a sub material which would be discussed by each group. In the third meeting, each group presented the results of their discussion. The last one was teachers provided daily trials to evaluate learning process. The results of this study showed that the process and learning outcomes of the art and culture materials with traditional music styles which were implemented on class VIII.3 by using cooperative learning method was very helpful in improving results of study and cooperation among group members. A structured learning plan could motivate the learners so that the learners ddi not get bored with learning that teachers provide. Giving the learning facilities to the learners and groups, giving a reward and assessment to individuals and groups could stimulate the learners in order to faster understanding and it was able to give motivation to the learners in achieving purpose of learning. Key Words: Application, Cooperative Learning Method, Art and Culture